Pyrolysis oil upgrading in high conversions using sub- and supercritical water above 400°C - Isa, Khairuddin Md; Snape, Colin E.; Uguna, Clement N.; Meredith, Will; Deng, Hui (Elsevier, 2016)
The upgrading of pyrolysis oil to bio-fuel was investigated using sub- and supercritical water at 410 and 450oC, with a high mass ratio of water to pyrolysis oil to ascertain the maximum yields that could be achieved. The results indicate that conversions increased with increasing pyrolysis oil to water mass ratio at high water ratio under supercritical water conditions at 410oC, gave the highest products conversion of ~91 wt. %, with 28 wt. % heavy oil recovered, ~23 wt. % gas yield, 27 wt. % water generated and approximately 13-14 wt. % of light oil produced. Similar product conversion was obtained using biomass as a feedstock with slightly higher water mass ratio added into the reactor (R1:15), and slightly lower heavy oil yield was recovered (21 wt. %). Gas generation was observed to reach a maximum and then level off at ~22-23 wt. % in near-supercritical water and supercritical water experiments at 410oC. No further cracking of the heavy oil was observed for experiments at 450oC, and an increase of 10 wt. % in the gas yield was observed when the temperature was increased to 450oC (33 wt. %) from 410oC (23 wt. %) with ~7 wt. % of light oil produced and approximately 24 wt. % of water generated. The oxygen contents of the heavy oil recovered were ~15-16 % (for 410 and 450oC), with H/C atomic ratios of 1.1. Similar overall conversions were achieved using tetralin with much lower solvent to oil ratios were needed and the liquid products had a slightly lower oxygen content (14 %). The estimated hydrogen from water was estimated as ca. 0.3 % at 410 and 450oC in high conversions of pyrolysis oil experiments, and experiments with tetralin/1-methyl naphthalene provide evidence that a small amount of hydrogen was sufficient to achieve high product conversion, giving an increase of H element content from 7.0 % to 7.3 %.